ANALISIS SEMIOTIKA PESAN MORAL PADA FILM KOREA PARASITE KARYA BONG JOON-HOO - ICHSAN , NUR (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2021)
The purposes of this study are: (1) What is the meaning of denotation in t he scene of Bong Joon-Hoo's Korean Film Parasite (2) What is the meaning of connotation in the scene of Bong Joon-Hoo's Korean Film Parasite (3) What is the moral message in the scene of the Korean film Parasite by Bong Joon-Hoo Bong Joon-Hoo. This research lasted for less than one month and is located in Makassar City. The research method used in this study is a qualitative research method. The informants in this study were three moviegoers. Data collection techniques through observation, interviews, and documentation. The theory used to analyze this research is Mass Communication Theory, and Semiotic Analysis by Roland Barthes which consists of the meaning of denotation, connotation, and moral message. The method used in this study means a qualitative method using informants (interviews). The research subject is the film Parasite which has a duration of 132 minutes which consists of 159 scenes and 8 scenes are the objects to be analyzed. As a result of this research, it is found that in Parasite there are many scenes or scenes that contain moral messages. Some of the moral messages that are divided into sub-themes/scene- scenes that the researcher chooses include discourses; First, there are rules of karma and the consequences for every action that is done, regardless of one's social status. second, a person's effort is the determinant of good or bad luck that he will experience, so humans should not depend only on luck and destiny. Third, the film Parasite talks about the cohesiveness of the family that must always be maintained because the family is the safest place for one to always return.